Toxicity of imidacloprid for stingless bees of the genus Tetragonisca (Meliponini) - Oliveira, Aline A.; Rodrigues, Andreia M. C.; Silva, Daniela M.; Oliveira, Marilene S.; de Souza, João C. P. [UNESP]; Dário, Bruno M. M.; Sousa, Leticia F.; Saraiva, Althiéris S. (Springer Nature, 2023)
Native bees are vital pollinators in the Neotropical Region and can serve as bioindicators for maintaining floral diversity in natural environments. However, the use of pesticides, specifically neonicotinoids, in agroecosystems has led to a decline in these pollinating organisms. This study aimed to evaluate the topical (contaminated mist) and residual (contaminated food) acute effect of the insecticide imidacloprid (IMI) on a stingless bee species (native to Brazil) with wide geographical distribution (Tetragonisca angustula) and two species restricted to certain regions (Tetragonisca fiebrigi and Tetragonisca weyrauchi) to determine LC10–48 h and LC50–48 h. The bees were exposed to various concentrations of IMI, in both topical and residual effect tests, and the results showed that low concentrations of the insecticide adversely affected the survival of all three species, with T. angustula being the most sensitive. The study also compared the sensitivity of the three species to the standard insecticide Dimethoate, and the results confirmed that T. angustula was the most sensitive. The findings of this study provide crucial ecotoxicological information, particularly concerning the residual effects of neonicotinoids on stingless bees. This evidence reinforces the urgent need to expand research on the effects of neonicotinoids on these important pollinators, so commonly found in nature and meliponaries. In addition, this research contributes significantly to filling the existing knowledge gap about the effects of pesticides on bee species native to Brazil, bringing to light the potential risks that these chemicals pose to the survival of these pollinators and emphasizing the urgent need for efforts of conservation in favor of these precious pollinating agents.
Keywords: Ecotoxicology; Non-target organisms; Residual effect; Survival; Topical effect